‘The New Order of Things’: Immobility as protection in the regime of immigration controls - Sharma, Nandita (Anti-Trafficking Review, 2017)
In this paper, I discuss two 1835 ordinances passed by the local council of the British colony of Mauritius. Passed shortly after Britain’s 1833 Slavery Abolition Act, these restrictions initiated the regulation and restriction of immigration within the British Empire. Seen as quite novel in their day, these ordinances employed the rhetoric of ‘protecting emigrants’ to legitimise the new constraints they imposed on free human mobility. Today, when the national ‘logic of constraint’ on human mobility is almost uncontested, the idea that immigration controls protect migrants remains central to the discursive practices concerning human trafficking. Nation-state constraints on human mobility are normalised while the exploitation and abuse of people on the move is ideologically redirected to ‘modern-day slavers’ or ‘evil traffickers’, thus absolving both the state and globally operative capital of their culpability.